Tradition of Distributing Inheritance Property in Communities of the City of Subulussalam in District District Maqashid Sharia Perspective - Zaini, Zaini; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to discuss the tradition of distributing inheritance among the people of Subulussalam City, especially in Penanggalan District from a maqashid sharia perspective. The type of research used is empirical research, meaning that the researcher goes directly into the community to obtain primary data through observation, interviews and documentation, and combined with secondary data such as books, the internet and other reading sources, then processed and analyzed to obtain a conclusion. The results of the research concluded that the distribution of inheritance among the people of Subulussalam City, especially in Penanggalan District, still uses customary law. In general, the people of Penanggalan District come from the Pakpak Batak ethnic group who adhere to a patrilineal family system, meaning that the male lineage takes precedence. However, in practice the distribution of inheritance does not adhere to this patrilineal system absolutely. The author found that there are two ways of dividing inheritance assets. First, sometimes assets are divided directly by parents while they are still alive in the form of a gift, to prevent disputes or quarrels between heirs in the future. Second, if the parents have died, the inheritance is divided peacefully through deliberation and consensus among the heirs. And traditions like this have become urf (custom), and they consider this tradition of distributing inheritance as quite good and considered fair. When viewed from the perspective of maqâshid syari'ah, the tradition of distributing inheritance like this fulfills the elements of benefit, especially in protecting the soul, offspring and property.